Pioneering women: the secondary school professor Rosario Fuentes - Fernàndez Gonzàlez, Jorge (Historia y Memoria de la Educación, 2021)
If higher education was already restricted and off-limits to women until the 20th century, their access to teaching and obtaining academic positions at these levels was even more difficult and complex. The aim of this paper is to describe a paradigmatic case of this problem: the life of Rosario Fuentes, who achieved the highest score in a public exam to become French professor and who became the first secondary school professor at the Zorrilla high school in Valladolid. Fuentes alsohad a relevant career as a translator, with contributions to texts on education, philosophy and psychology. This study highlights her role as a researcher associated with the Junta para la Ampliación de Estudios (Board for Advanced Studies) and as a writer of French textbooks. She also took part in the organization of language teachers as well as teaching in different Teacher Training Schools. Her career suffered as a result of the purging process which Franco’s dictatorship carried out on teachers, a process that was especially arbitrary against women due to the fact that their own actions and thoughts were often considered less relevant than those of their partners or relatives.. This paper, which examines many of these aspects of her life, relies on documentation and unpublished images from different archives such as those of the administration and the family, as well as previous works that analyse the issue of women teachers in Secondary Education.